The Effects of Workplace Stressors on Stress and Subjective Well-Being of Female Myanmar Migrant Workers in Thailand Mediated by Coping Strategies and Social Support - Aung, Nant Mu Mu Aung; Varma, Parvathy (Scholar: Human Sciences, 2021)
The current study attempted to investigate the direct and indirect effects of workplace stressors on stress and subjective well-being of female Myanmar migrant workers in Thailand mediated by coping strategies and social support. This study employed a quantitative method with a correlational research design, using a path model. A convenience sampling through self-administered survey questionnaires was given to a total of 200 female Myanmar migrant workers in Bangkok and Samut Sakhon areas. The results showed that there was a direct effect of a workplace stressor on stress and subjective well-being. Stressor of workplace injustices and barriers to exit job was associated with increased levels of stress and decreased levels of subjective well-being. There was an indirect effect of workplace stressor of coercive working conditions on stress mediated by problem-focused coping strategies. Similarly, emotion-focused coping strategies mediated the relationship between coercive working conditions and stress as well as subjective well-being. Social support was negatively associated with stress and positively associated with subjective well-being. Moreover, Problem-focused coping strategies and perception about social support lessened the stress and promoted the subjective well-being of female Myanmar migrant workers in Thailand.